Metals and alloys industrial applications - Benvenuto, Mark A. (Mark Anthony) (De Gruyter graduate., 2016)
This book examines the processes performed by industry to extract metals, discusses at how such chemical processes affect every-day life, examines what alloys are produced and used, looks at what waste is produced as metals are made, and illustrates chemical processes in which industry has made strides to improve or "green" their production.